The compendium of Arabidopsis thaliana GLYCINE-RICH RNA-BINDING PROTEIN 8 in vivo targets determined by iCLIP - Katja Meyer; Martin Lewinski; Tino Köster; Dorothee Staiger (Scientific Data)
Abstract RNA-binding proteins impact RNA processing including splicing, translation and RNA decay to dictate the fate of RNAs. Thus, insights into RNA-protein interactions in the cell provide insights into regulatory networks regulating gene expression at the posttranscriptional level. In higher plants, only few RNA-binding proteins have their in vivo targets and binding sites determined, mostly due to technical challenges posed by plant tissue. We previously adapted individual nucleotide-resolution crosslinking and immunoprecipitation that relies on UV-light irradiation to stabilize RNA-protein interactions in the cell to Arabidopsis plants. Here, we profiled the in vivo binding landscape of the glycine-rich RNA-binding protein AtGRP8 by iCLIP. Transgenic plants expressing AtGRP8 fused to GREEN FLUORESCENT PROTEIN under the native promoter were subjected to UV-crosslinking. RNA-protein complexes were immunoprecipitated and bound RNAs were determined by RNA-seq. A bioinformatics pipeline tailor-made for Arabidopsis identified target RNAs, and delineated binding sites and binding motifs for AtGRP8. These data will aid in assembling a compendium of binding sites for plant RNA-binding proteins and contribute to unravel plant posttranscriptional networks.